2022
DOI: 10.1186/s13018-022-03305-z
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating effect of Shilajit on osteogenic property of adipose-derived mesenchymal stem cells (ASCs)

Abstract: Background Shilajit has been widely used remedy for treating a numerous of illness such as bone defects in Iran traditional folk medicine since hundreds of years ago. The aim of the present study was to explore the effect of Shilajit on the osteogenic differentiation of human adipose-derived mesenchymal stem cells (ASCs) in two- (2D) and three-dimensional (3D) cultures. Materials and methods ASCs were seeded in 3D 1% alginate (Alg) hydrogel with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…[25] In a study by Kangari et al, Shilajit showed that Alg hydrogel accelerated the differentiation of human fat-derived mesenchymal stem cells into osteoblasts without changing their physical properties. [26] Another study showed that Shilajit was given systemically to individuals with tibial and femoral fractures, and compared to placebo groups, this expedited bone formation. [27] SCI has evolved as one of the most severe illnesses, having a significant influence on global health-care systems.…”
Section: Discussionmentioning
confidence: 99%
“…[25] In a study by Kangari et al, Shilajit showed that Alg hydrogel accelerated the differentiation of human fat-derived mesenchymal stem cells into osteoblasts without changing their physical properties. [26] Another study showed that Shilajit was given systemically to individuals with tibial and femoral fractures, and compared to placebo groups, this expedited bone formation. [27] SCI has evolved as one of the most severe illnesses, having a significant influence on global health-care systems.…”
Section: Discussionmentioning
confidence: 99%
“…Shilajit has shown greater cell viability for osteoblasts as compared to stem cells. As shilajit is a source of mineral ingredients like Ca and Mg, which play a key role in promoting osteogenesis which induce Ca deposition and promote bone mineralization and osteogenesis [33]. Moreover, Shajit has a potential to enhance bone formation through synthesis of nucleic acids, polysaccharides, proteins and hormones as they are needed for cell and tissue growth.…”
Section: In-vitro Cytotoxicity Assaymentioning
confidence: 99%
“…Sexual health benefits: Mumio has been found to have potential benefits for sexual health. One study published in the Journal of Sexual Medicine found that mumio improved erectile dysfunction in male rats (Kaur et al 2013;Kangari et al, 2022).…”
Section: Uses Of Mumio In Traditional Medicinementioning
confidence: 99%